Wheat-Related Disorders in Children: A 360-Degree View - Michele Fingerle; Sebastiano Salaorni; Angelo Pietrobelli; Giorgio Piacentini; Claudia Banzato; Luca Pecoraro (MDPI AG, 2024)
Immunological illnesses related to wheat represent an epidemiologically relevant phenomenon at a pediatric age. The term "Wheat-related disorders" involves a spectrum of diseases: celiac disease, IgE-mediated wheat allergy, non-IgE mediated wheat allergy, wheat-related eosinophilic esophagitis, and non-celiac gluten sensitivity. Their pathogenesis is different. At the same time, wheat represents their common point. This article aims to the state-of-the-art and new clinical evidence in pediatric age.